The practical, ethical and legal reasons why patients should not be transferred between NHS trusts for phage therapy. Issue 6 (December 2022) - Jones, Joshua D; Ferguson, Pamela R; Suleman, Mehrunisha
Bacteriophages (phages) are naturally occurring viruses of bacteria that have a long history of use as antimicrobials, known as phage therapy. The antibiotic resistance crisis has driven renewed interest in phage therapy, which has been used on an unlicensed compassionate basis in various Western contexts. The option to use unlicensed medicines exists to allow clinicians to respond to genuine clinical needs arising in their own patients. However, in the UK some clinicians may, in the absence of suitable patients of their own, seek to transfer patients from other NHS trusts into their own Trust. This article sets out why patient transfer is not necessary and the practical, ethical and legal reasons why patients should not be transferred between NHS Trusts for phage therapy. Phage preparations should always be transported to the patient and the patient treated in the Trust in which they would have received care in the absence of phage. We enclose suggested best practice guidelines for adoption across the UK that will protect patient safety and safeguard clinicians and Trusts from potential litigation.